Dos and don'ts in large animal models of aortic insufficiency - Weisskopf, Miriam; Glaus, Lukas; Trimmel, Nina E.; Hierweger, Melanie M.; Leuthardt, Andrea S.; Kukucka, Marian; Stolte, Thorald; Stoeck, Christian T.; Falk, Volkmar; Emmert, Maximilian Y.; Kofler, Markus; Cesarovic, Nikola (Frontiers in Veterinary Science, 2022)
Aortic insufficiency caused by paravalvular leakage (PVL) is one of the most feared complications following transcatheter aortic valve replacement (TAVI) in patients. Domestic pigs (Sus scrofa domestica) are a popular large animal model to study such conditions and develop novel diagnostic and therapeutic techniques. However, models based on prosthetic valve implantation are time intensive, costly and often hamper further hemodynamic measurements such as PV-loop and 4D MRI flow by causing implantation-related wall motion abnormalities and degradation of MR image quality. This paper describes in detail, the establishment of a minimally invasive porcine model suitable to study the effects of mild to moderate “paravalvular“ aortic regurgitation on left ventricular (LV) performance and blood flow patterns, particularly under the influence of altered afterload, preload, inotropic state and heart rate. Six domestic pigs (Swiss large white, females, 60-70 kg of body weight) were used to establish this model. Defects on the hinge point of aortic leaflets and annulus were created percutaneously by pierce-and-dilate technique either in the right coronary cusp (RCC) or in the non-coronary cusp (NCC). Hemodynamic changes as well as LV performance were recorded by PV-loop measurements, while blood flow patterns were assessed by 4D MRI. LV performance was additionally challenged by pharmaceutically altering cardiac inotropy, chronotropy and afterload. The presented work aims to elaborate the dos and don'ts in porcine models of aortic insufficiency and intends to reduce the learning curve for researches planning to use this or similar models by giving valuable insights ranging from animal selection, to vascular access choices, placement of PV Loop catheter, improvement of PV Loop data acquisition and post processing and finally the induction of paravalvular regurgitation of the aortic valve by a standardized and reproducible balloon induced defect in precisely targeted region of the aortic valve.